Corrigendum to “Adulteration in paneer (Indian cottage cheese): A review of practices, detection, and public health implications – a critical analysis”[Food Control 187 (2026) 112163] - A. Surendra Babu; P. Sankarganesh; V. Parthasarathy; K. Rajkumar; Meenatai Gunderao Kamble (Food Control, 2026)

Human and Porcine Marginal Chordal Forces in a Vacuum Based Physiological In Vitro Mitral Valve Model - Mads V. Ancker; Sam E. Stephens; Justin T. Jack; Neil B. Ingels; Jonathan F. Wenk; Søren N. Skov; Surendra K. Chawla; Ajit. P. Yoganathan; Morten O. Jensen (Cardiovascular Engineering and Technology, 2026)
Introduction This study aimed to quantitatively investigate the role of marginal chordae of the mitral valve during static closure by analyzing the force within these chordae and its potential correlation with the transvalvular pressure. Materials and Methods Porcine (n = 10) and human (n = 4) mitral valves were mounted in a saddle-shaped annulus clamp, while an in vitro system was utilized to replicate a physiological systolic blood pressure by vacuum pressure applied to the atrial side of the valve. A Millar pressure catheter and force transducers (“C-gauges”) were used to acquire the data. Strut chordal force was recorded simultaneously with the marginal chordal force, to serve as a verification of the employed equipment. Results The marginal chordal force in porcine and human averaged to 0.012 N ± 0.008 N and 0.006 N ± 0.008 N respectively at peak systolic pressure of 120 mmHg. Additionally, a simplified finite element study was conducted and supports low marginal forces relative to intermediary chords. Discussion & Conclusion This low force calls into question the traditionally-described role of the marginal chordae in preventing mitral prolapse at closure. The chords do, however, still show signs of assisting with the leaflets’ positioning. The relationship between marginal chordal forces and transvalvular pressure varies significantly across experiments, further obfuscating their role in normal valvular function.

Adulteration in paneer (Indian cottage cheese): A review of practices, detection, and public health implications – a critical analysis - A. Surendra Babu; P. Sankarganesh; V. Parthasarathy; K. Rajkumar; Meenatai Gunderao Kamble (Food Control, 2026)

In silico design, synthesis of a novel chalcone derivative and its in vitro and in vivo anticancer activity against colon cancer-induced mouse model - Uday Raj Sharma; Sushavan Roy; Gurubasavaraja Swamy Purawargaar Matada; Manjunatha P M; Suresh Janadri; Surendra Vada; T. Haribabu; Nageena Taj; Gayathri S V; Rohit Pal; Susovan Das; Nirmal Chanda (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Application of industrial internet of things (IIoT) in food processing industries - A. Adithi Arya; V. Parthasarathy; A. Surendra Babu; P. Sankarganesh (Trends in Food Science & Technology, 2025)

Split quadrant mosaic algorithm: a novel approach to develop multi-model ensemble for wind resource assessment - Garlapati Nagababu; Preksha Patwa; Harish Puppala; V. V. Arun Kumar Surisetty; Surendra Singh Kachhwaha; Rashmi Sharma (Climate Dynamics, 2025)

Efficacy and Economic Viability of Biopolymer-Based Trichoderma as a Sustainable Alternative to Emerging Fungicides for Managing Safflower Soil-Borne Diseases - P. Surendra; Suma Moka; M. Kavya; R. D. Prasad; K. S. V. P. Chandrika; D. Murumkar; Reddy T. Rajeshwar; N. Prabhavathi; C. V. Ambadkar; L. Tandon Ashwarya (Journal of Crop Health, 2025)

Plant diversity and microbial interaction on soil carbon stock in the tropical homegardens: a nature-based solution to climate change - Athulya Tom; V. Divya Vijayan; T. K. Kunhamu; S. Sandeep; K. Surendra Gopal; V. Jamaludheen; B. R. Vishnu (Agroforestry Systems, 2025)

Senescence-associated genes (SAGs) in cotton: Genome-wide identification, phylogenetic, and expression analyses provide insight into their role in development and stress response - Varsha Singh; Maninder Singh; Tikshana Yadav; Rishi Kumar Verma; Mamta Yadav; Vijay Pratap Singh; Samir V. Sawant; Surendra Pratap Singh (South African Journal of Botany, 2025)

Immune Mechanisms in Alzheimer’s Disease: The Role of Toll-Like Receptors Signalling - Dinisha Sharma; P. M. Manjunatha; T. Hari Babu; Arpan Dhungel; Sushree Swaraj; Suresh Janadari; Uday Raj Sharma; V. Surendra; Nageena Taj; S. V. Gayathri (Current Pharmacology Reports, 2024)

Evaluation of chicory leaf extract on chronic kidney disease model in streptozotocin-induced diabetic nephropathy - Simran Sultana; Uday Raj Sharma; Reddibathina Leela Haripriya; Athira Ramachandran; Runashree Borah; V. Surendra; T. Haribabu; S. V. Gayathri; Suresh Janadri; P. M. Manjunatha (Advances in Traditional Medicine, 2024)

Consequences of Local Conspecific Density Effects for Plant Diversity and Community Dynamics - Joseph A. LaManna; Florian Hartig; Jonathan A. Myers; Robert P. Freckleton; Matteo Detto; Akshay Surendra; Cole J. Doolittle; Bénédicte Bachelot; Robert Bagchi; Liza S. Comita; David M. DeFilippis; Nohemi Huanca‐Nunez; et al. (Ecology Letters, 2024)
Conspecific density dependence (CDD) in plant populations is widespread, most likely caused by local‐scale biotic interactions, and has potentially important implications for biodiversity, community composition, and ecosystem processes. However, progress in this important area of ecology has been hindered by differing viewpoints on CDD across subfields in ecology, lack of synthesis across CDD‐related frameworks, and misunderstandings about how empirical measurements of local CDD fit within the context of broader ecological theories on community assembly and diversity maintenance. Here, we propose a conceptual synthesis of local‐scale CDD and its causes, including species‐specific antagonistic and mutualistic interactions. First, we compare and clarify different uses of CDD and related concepts across subfields within ecology. We suggest the use of local stabilizing/destabilizing CDD to refer to the scenario where local conspecific density effects are more negative/positive than heterospecific effects. Second, we discuss different mechanisms for local stabilizing and destabilizing CDD, how those mechanisms are interrelated, and how they cut across several fields of study within ecology. Third, we place local stabilizing/destabilizing CDD within the context of broader ecological theories and discuss implications and challenges related to scaling up the effects of local CDD on populations, communities, and metacommunities. The ultimate goal of this synthesis is to provide a conceptual roadmap for researchers studying local CDD and its implications for population and community dynamics.

Rheumatoid arthritis-associated complications during pregnancy and its effect on offspring: comprehensive review - S. Rohini; Uday Raj Sharma; M. Vinutha; D. Shreelaxmi; Surendra Vada; Suresh Janandri; T. Haribabu; Nageena Taj; S. V. Gayathri; Abhishek Ghara; Manjunatha P. Mudagal (Inflammopharmacology, 2024)

Genome-wide identification and expression analysis of autophagy-related genes (ATG) in Gossypium spp. reveals their crucial role in stress tolerance - Mamta Yadav; Garima Saxena; Rishi Kumar Verma; Mehar H. Asif; Vijay Pratap Singh; Samir V. Sawant; Surendra Pratap Singh (South African Journal of Botany, 2024)

Variability of Particulate Amino Acids and Processes Responsible for Sources into the Coastal Waters of the Bay of Bengal - B. S. K. Kumar; D Bhaskara Rao; T. Surendra; Ch. V. Rao; M. P. Meshram (Estuaries and Coasts, 2024)

Green engineered synthesis of PbxZn1-xO NPs: An efficient electrochemical sensor and UV light-driven photocatalytic applications - M. Dinamani; B.S. Surendra; H.C. Ananda Murthy; N. Basavaraju; Vijaya V. Shanbhag (Environmental Nanotechnology, Monitoring & Management, 2023)

Removal of hardness using natural and synthetic water treatment system for safe and sustainable water supply in the Indian context - M. S. Madhusudhan; H. J. Surendra; H. J. Rajendra; V. Chinmay; U. S. Udaygowda (Sustainable Water Resources Management, 2023)

Comparing the Organic Carbon Fractions in Composts of Agricultural Wastes at Different Temperatures and Stages - Ajit Kumar Meena; Dnyaneshwar V. Mali; Ram Swaroop Meena; Surendra Singh Jatav; Ram Hari Meena; Jitendra Singh Bamboriya; Premlata Meena; Shyam D. Jadhao; Abed Alataway; Ahmed Z. Dewidar; Mohamed A. Mattar (Journal of Soil Science and Plant Nutrition, 2023)

Brucella melitensis: Divergence Among Indian Strains and Genetic Characterization of a Strain Isolated from Cattle - Hariprasad Naidu Gonuguntla; Kota Sri Naga Leela Surendra; Amitesh Prasad; Laxmi Narayan Sarangi; Samir Kumar Rana; Gujjala Manasa; Ponnanna Nadikerianda Muthappa; A. V. Harikumar; Girish Kumar Sharma (Indian Journal of Microbiology, 2023)

SAtellite-based Marine Process Understanding, Development, Research and Applications for Blue Economy (SAMUDRA): A Technology Demonstration Program in the Bay of Bengal - Rashmi Sharma; Neeraj Agarwal; Ratheesh R; Surisetty VVArun Kumar; A. D. Rao; KVSR Prasad; Jaya Kumar Seelam; R. Mani Murali; V. Suneel; Surendra Singh K; R. K. Sarangi; Soba J. Kizhakudan; et al. (Journal of the Indian Society of Remote Sensing, 2023)

Techno-economic Analysis of Wave Energy Resource for India - Ravi P. Patel; Garlapati Nagababu; Surendra Singh Kachhwaha; V. V. Arun Kumar Surisetty; M. Seemanth (Journal of the Indian Society of Remote Sensing, 2023)

Consequential rice crop response to resultant soil properties in a toposequence in eastern coastal plain of Odisha, India - Ramasamy Srinivasan; Dulal Chandra Nayak; Rajendran Gobinath; Subbanna Naveen Kumar; D. V. K. Nageswara Rao; Surendra Kumar Singh (Modeling Earth Systems and Environment, 2022)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Correction to: Synergies and trade-offs for climate-resilient agriculture in India: an agro-climatic zone assessment - Naveen P Singh; Bhawna Anand; Surendra Singh; S K Srivastava; Ch Srinivasa Rao; K V Rao; S K Bal (Climatic Change, 2021)

Synergies and trade-offs for climate-resilient agriculture in India: an agro-climatic zone assessment - Naveen P Singh; Bhawna Anand; Surendra Singh; S K Srivastava; Ch Srinivasa Rao; K V Rao; S K Bal (Climatic Change, 2021)

Altered Kinetics Properties of Erythrocyte Lactate Dehydrogenase in Type II Diabetic Patients and Its Implications for Lactic Acidosis - Aniket V. Mali; Sunita S. Bhise; Surendra S. Katyare; Mahabaleshwar V. Hegde (Indian Journal of Clinical Biochemistry, 2018)

SBAS-derived TEC maps: a new tool to forecast the spatial maps of maximum probable scintillation index over India - Surendra Sunda; Sneha Yadav; R. Sridharan; M. S. Bagiya; P. V. Khekale; Pan Singh; S. V. Satish (GPS Solutions, 2017)

Putative Role of Cardio Metabolic Risk Among Poorly Controlled Asthmatics in South Indian Population - Murugaiyan Sathish Babu; K. P. Sreesoorya; Surendra K. Menon; Subiman Saha; A. R. Srinivasan; S. Arul Vijaya Vani; R. Reeta; V. Kuzhandai Velu (Indian Journal of Clinical Biochemistry, 2017)

Altered Erythrocyte Glycolytic Enzyme Activities in Type-II Diabetes - Aniket V. Mali; Sunita S. Bhise; Mahabaleshwar V. Hegde; Surendra S. Katyare (Indian Journal of Clinical Biochemistry, 2016)

Marker-assisted introgression of a QTL region to improve rust resistance in three elite and popular varieties of peanut (Arachis hypogaea L.) - Rajeev K. Varshney; Manish K. Pandey; Pasupuleti Janila; Shyam N. Nigam; Harikishan Sudini; M. V. C. Gowda; Manda Sriswathi; T. Radhakrishnan; Surendra S. Manohar; Patne Nagesh (Theoretical and Applied Genetics, 2014)

A new species of Abelmoschus Medik. (Malvaceae) from Chhattisgarh, India - Shrikant Sutar; Pravin Patil; Makarand Aitawade; Joseph John; Surendra Malik; Satyawada Rao; Shrirang Yadav; K. V. Bhat (Genetic Resources and Crop Evolution, 2013)

Influence of salicylic acid and methyl jasmonate elicitation on anthocyanin production in callus cultures of Rosa hybrida L. - Mohan Ram; K. V. Prasad; S. K. Singh; B. S. Hada; Surendra Kumar (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Structural and hydrological alterations of soil due to addition of coal fly ash - Isa A. M. Yunusa; V. Manoharan; Inakwu O. A. Odeh; Surendra Shrestha; C. Greg Skilbeck; Derek Eamus (Journal of Soils and Sediments, 2011)

Induction of anthocyanin pigments in callus cultures of Rosa hybrida L. in response to sucrose and ammonical nitrogen levels - Mohan Ram; K. V. Prasad; Charanjit Kaur; S. K. Singh; Ajay Arora; Surendra Kumar (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Leucine125Valine (Leu125Val) Gene Polymorphism of Platelet Endothelial Cell Adhesion Molecule-1 (PECAM-1) and Myocardial Infarction in Indian Population - Kavita K. Shalia; Manoj R. Mashru; Surendra L. Soneji; Vinod K. Shah; Satchidanand Payannavar; Amar Walvalkar; Rajashree A. Mokal; Shilpa M. Mithbawkar; Ketki V. Kudalkar; Ajin Abraham; Priti K. Thakur (Indian Journal of Clinical Biochemistry, 2010)

Effect of gamma irradiation on microbial load, aflatoxins and phytochemicals present in Trigonella foenum-graecum - Prakash C. Gupta; Vivek Bajpai; V. Mishra; R. K. Saxena; Surendra Singh (World Journal of Microbiology and Biotechnology, 2009)

Comparative study of a Zn-enriched post-methanation bio-sludge and Zn sulfate as Zn sources for a rice–wheat crop rotation - Prakash C. Srivastava; Ajay P. Singh; Surendra Kumar; V. Ramachandran; Manoj Shrivastava; S. F. D’souza (Nutrient Cycling in Agroecosystems, 2009)

Desorption and transformation of zinc in a mollisol and its uptake by plants in a rice–wheat rotation fertilized with either zinc-enriched biosludge from molasses or with inorganic zinc - Prakash C. Srivastava; Ajay P. Singh; Surendra Kumar; V. Ramachandran; Manoj Shrivastava; S. F. D’souza (Biology and Fertility of Soils, 2008)